Mediator subunit MED25 links the jasmonate receptor to transcriptionally active chromatin - An, Chunpeng (Proc Natl Acad Sci U S A, 2017)
Jasmonoyl-isoleucine (JA-Ile), the active form of the plant hormone jasmonate (JA), is sensed by the F-box protein CORONATINE INSENSITIVE 1 (COI1), a component of a functional Skp–Cullin–F-box E3 ubiquitin ligase complex. Sensing of JA-Ile by COI1 rapidly triggers genome-wide transcriptional changes that are largely regulated by the basic helix–loop–helix transcription factor MYC2. However, it remains unclear how the JA-Ile receptor protein COI1 relays hormone-specific regulatory signals to the RNA polymerase II general transcriptional machinery. Here, we report that the plant transcriptional coactivator complex Mediator directly links COI1 to the promoters of MYC2 target genes. MED25, a subunit of the Mediator complex, brings COI1 to MYC2 target promoters and facilitates COI1-dependent degradation of jasmonate–ZIM domain (JAZ) transcriptional repressors. MED25 and COI1 influence each other’s enrichment on MYC2 target promoters. Furthermore, MED25 physically and functionally interacts with HISTONE ACETYLTRANSFERASE1 (HAC1), which plays an important role in JA signaling by selectively regulating histone (H) 3 lysine (K) 9 (H3K9) acetylation of MYC2 target promoters. Moreover, the enrichment and function of HAC1 on MYC2 target promoters depend on COI1 and MED25. Therefore, the MED25 interface of Mediator links COI1 with HAC1-dependent H3K9 acetylation to activate MYC2-regulated transcription of JA-responsive genes. This study exemplifies how a single Mediator subunit integrates the actions of both genetic and epigenetic regulators into a concerted transcriptional program.